Effect of using two-step thermal annealing with different ambient gas on Mg activation and crystalline quality in GaN. (June 2015) - Azimah, E.; Zainal, N.; Shuhaimi, A.; Hassan, Z.
Highlights: Improvement of Mg activation in GaN was obtained via two-step thermal annealing. Oxygen-annealing at the first step can break passivated Mg–H bonds in GaN. Nitrogen-annealing at the second step has improved GaN crystal structure. Abstract: Two-step thermal annealing with different ambient gas was proposed to improve the activation of Mg doping in MOCVD-GaN films; (1) with nitrogen at the first step and followed by oxygen (N2 /O2 ) and (2) with O2 and then by N2 (O2 /N2 ). For comparison, two samples annealed in one-step thermal annealing using air and N2, respectively were also prepared. From Hall-effect measurement, the two-step annealing with the use of O2 /N2 treatment was found to give the highest hole concentration at to 5.5 × 10 17  cm −3 . On the other hand, Raman spectroscopy and XRD measurements revealed that the O2 /N2 annealed sample exhibited the smallest compressive strain and FWHM (full width at high maximum) compared to others. Hence, the annealing with O2 /N2 is proposed to be the most promising technique that not only to increase the hole concentration effectively but also to improve the crystalline quality of the samples.